Depicting the discrepancy between Tri genotype and chemotype on the basis of strain CBS 139514 from a field population of F. graminearum sensu stricto from Argentina - Kulik, Tomasz (2016)
Recent studies on a field population of F. graminearum sensu stricto from Argentina revealed an atypical panel of strains identified through PCR genotyping as 15ADON genotypes, but producing high levels of 3ADON. Based on representative strain CBS 139514, we asked if the discrepancy between trichothecene genotype and chemotype might result from inter-chemotype recombination of the chemotype-determining genes. To answer this, we sequenced the complete core Tri gene cluster (around 30,200 bp) from this strain and compared its sequence to sequence data of typical type B trichothecene genotypes/chemotypes. Sequence alignment showed that CBS 139514 has an identical sequence within the entire core Tri cluster to the 15ADON genotype. The revealed discrepancy underlines the need for using both molecular and chemical methods for reliable characterization of toxigenic strains of Fusarium.